2017
DOI: 10.18632/oncotarget.16399
|View full text |Cite
|
Sign up to set email alerts
|

Serum CD166: A novel biomarker for predicting nasopharyngeal carcinoma response to radiotherapy

Abstract: The present study aimed to identify whether CD166 can be used as a biomarker for predicting the response of nasopharyngeal carcinoma (NPC) to radiotherapy. The serum concentration of CD166 in patients with NPC were detected by enzyme-linked immunosorbent assay. The secreted level of CD166 with radioresistant NPC was significantly higher than that with radiosensitive NPC. In vitro, the CD166 positive rate in the CNE2 cell membrane was significantly lower than that in the CNE2R cell membrane. The magnetic-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…All experiments were conducted three times. Dose–response curves were analyzed using the multitarget single-hit model in the GraphPad Prism 5.0 software 13 , 14 with the formula: Survival fraction (SF)=1 − (1 − e − D / D 0 ) N , where D 0 (mean lethal dose) is the single dose of radiation that kills 63% of cells, N represents the number of intracellular radiosensitive areas; Dq (lnN * D 0 ) is the required threshold for cell damage. When the Dq increases, the survival curve area is widened, and radioresistance is increased.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were conducted three times. Dose–response curves were analyzed using the multitarget single-hit model in the GraphPad Prism 5.0 software 13 , 14 with the formula: Survival fraction (SF)=1 − (1 − e − D / D 0 ) N , where D 0 (mean lethal dose) is the single dose of radiation that kills 63% of cells, N represents the number of intracellular radiosensitive areas; Dq (lnN * D 0 ) is the required threshold for cell damage. When the Dq increases, the survival curve area is widened, and radioresistance is increased.…”
Section: Methodsmentioning
confidence: 99%
“…The serum level of CD166/ALCAM in patients with radiation-resistant tumors was higher than that of radiation-sensitive patients; at the cell membrane level, it has been proven that CNE-2 and CNE-2R cells with high expression of CD166/ALCAM had a lower radio-sensitivity than those of CNE-2 and CNE-2R with negative expression. In addition, the expression of CD166/ALCAM was correlated with the radio-sensitivity of NPC 14. In the present study, we applied lentivirus-mediated shRNA to downregulate CD166/ALCAM in CNE-2R cell line.…”
Section: Discussionmentioning
confidence: 80%
“…Our research group identified differentially secreted proteins in the cultured NPC radio-resistant cell line CNE-2R and its parental cell line CNE-2 by proteomics-related identification technique in vitro. Besides, CD166 is positively expressed in CNE-2R, while is negatively expressed in CNE-2; higher expression could also be observed in patients’ serum being radio-resistant NPC than that in radiation-sensitive patients;13 we found that the sensitivity of radiation of NPC cells with positive expression of CD166 is not comparable to that of NPC cells with negative expression 14. It is suggested that the expression of CD166 in the cell membrane is associated with radio-sensitivity of NPC cells.…”
Section: Introductionmentioning
confidence: 66%
“…Radiotherapy is a mainly treatment for nasopharyngeal carcinoma (NPC). However, radioresistance is one of the major factors to affect the therapeutic efficacy and prognosis of patients [13]. Accordingly, identifying potential biomarkers and studying the molecular mechanisms associated with radioresistant nasopharyngeal carcinoma has become a hot topic both in basic and clinical research.…”
Section: Introductionmentioning
confidence: 99%